STRATEGI PERCEPATAN PENCAPAIAN TARGET MILLENIUM DEVELOPMET GOALS (MDGS) DI KOTA MALANG - Nuraini, Ida; Susilowati, Dwi (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2015)
The purpose of this study is a map of the readiness of Malang in achieving the MDGs by 2015 and the right strategy based on SWOT analysis to accelerate the achievement of the target MDGs.Dari can be concluded that the MDG targets by 8 item in Malang in 2015 still can not be reached. The number of poor people was 43,400 people, the open unemployment of 5.19% (22.185%). The adult literacy rate of 4.57% or 34 717 persons. Percentage of the population 10 years and over who do not have a diploma of 21.21%, finished primary school / MI amounted to 23.77% and 18.17% of junior high school graduation. In the field of gender equality, the contribution of women in politics is still very low. In the health field there are still 245 the number of infant deaths and 10 cases of maternal mortality. People with HIV and March 2013 reached 2,134 and AIDS as many as 341 people with high risk factors through needle drugs and high risk in men (65%) at the age of 25-49 years. The field of environmental sustainability in some respects much decreased as the quality of drinking water, air quality and temperature.